Stand-alone anterior lumbar interbody fusion: indications, techniques, surgical outcomes and complications. (1st December 2016) - Kerolus, Mena; Turel, Mazda K; Tan, Lee; Deutsch, Harel
ABSTRACT: Introduction : Anterior lumbar interbody fusion (ALIF) is a well-established technique to achieve lumbar spine fusion with various indications including degenerative disk disease, spondylolisthesis, recurrent disk herniation, adjacent level disease, pseudoarthrosis, as well as being used as part of the overall strategy to restore sagittal balance. ALIF can be an extremely useful tool in any spine surgeon's armamentarium. However, like any surgical procedure, proper patient selection is key to success. A solid understanding of the biomechanics, careful surgical planning, along with clear knowledge of the advantages and disadvantages of stand-alone ALIF will ensure optimal clinical outcome. Stand-alone ALIF may be a suitable surgical option in carefully selected patients that can provide good clinical results and adequate fusion rates without the need for posterior instrumentation. Areas covered : A brief overview of the indications, techniques, biomechanics, surgical outcome and complications of stand-alone ALIF is provided in this article with a review of the pertinent literature. Expert commentary : In this review we discuss the clinical evidence of using a stand-alone ALIF compared to other fusion techniques of the lumbar spine. The development of interbody cages with integrated screws has increased the arthrodesis rate and improved clinical outcomes while decreasing morbidity and operative time.